Bite detector / Karim Sadiran - Sadiran, Karim (1998)
This project is to design an electronic bite detector fishing rod. The detector is intended to be integrated into commercially available fishing rod. The electronic bite detector fishing rod, without any other additional equipment, will enabie the angler to receive detect signal of fish bite even in a very poor light condition. The design will not change the original characteristic of the rod.